Em nome do sagrado: os casos de pedofilia na Igreja Católica da Paraíba na imprensa - Ferreira, Joana Rosa Henrique (2020)
In 2013, the newspaper “Jornal da Paraíba” published their first article bringing complaints about pedophilia cases involving the state Archdiocese. After three years of coverage of the newspaper, Dom Aldo Pagotto, the Archbishop at the time, had his order suspended and resigned. This paper presents the coverage of the case, the importance of the trust relationship between reporter and source, how was the research work of reporter Valéria Sinésio during the production of the stories and how the reports impacted her social and professional life, after having signed the articles. Data collection was conducted through interviews with the reporter and other professionals from the “Jornal da Paraíba” journalism team, from February 2018 to November 2019. The results of the analysis show that the tension of the report, added to the load of Journalism's own work in modern times, creates an environment conducive to illness. Physical and mental symptoms, such as insomnia, anxiety, nervousness and weight loss were reported during the period of journalistic investigation, corroborating with other studies that state the high degree of danger to which journalism professionals are subjected.